Estágios foliares, fenologia da seringueira (Hevea spp.) e interação com Microcyclus ulei (mal das folhas) - Sambugaro, Rosana [UNESP] (2007)
The rubber tree is a tropical species that loses its leaves periodically. This deciduifolio habit is an important character for the rubber tree, that is, clones uniform defoliation provides a reduction in the pathogens inocule whose reproductive structures are located in the old leaves. After defoliation, it occurs the foliar renewal and it is at this stage, also known as refoliation, that the rubber tree presents susceptible leaflets in which occur most part of the foliar deseases, such as leaf blight, where the cycle of the pathogen (Microcyclus ulei (P. Henn.)v. Arx) is straightly related with the foliar stages (B, C and D). Therefore, the knowledge on these stages, clones phenologic behavior, factors that influence this character and local climate conditions is important for their selection. The objectives of this work were: characterize through quantitative and descriptive foliar morphology the stages B, C and D; characterize the phenologic behavior and the incidence of South American Leaf Blight; correlate the beginning of the defoliation period with climatic parameters, and leaf blight incidence, during the foliar renewal period, with climatic parameters. For the stages characterization, it was used the clone PB 235, from which the leaves central leaflets were collected, at different stages. It was measured the foliolar limbus lenght, width and area, and the petiole lenght and diameter. It was also determined the form of the limbus, apex and base of the foliolar lamina, as well the leaf coloration. For the other objectives, the clones Fx 3844, Fx 3864, Fx 2261, IAN 873, IAN 717 and RRIM 600 of rubber trees from Vale do Ribeira region, São Paulo state were used, being the fallen leaflets collected weekly in four baskets by clone, randomly distributed. The leaflets were totalized, separated by age and analyzed as for the incidence of the fungus Microcyclus ulei... (Complete abstract click electronic access below)